Carbohydrate and caffeine improves high-intensity running of elite rugby league interchange players during simulated match play. - Clarke, J. S.; Highton, J.; Close, G. L.; Twist, C. (The Journal of Strength and Conditioning Research, 2019)
The study examined the effects of carbohydrate and caffeine ingestion on simulated rugby league interchange performance. Eight male elite rugby league forwards completed 2 trials of a rugby league simulation protocol for interchange players 7 days apart in a randomized crossover design, ingesting either carbohydrate (CHO; 40 g·h-1) or carbohydrate and caffeine (CHO-C) (40 g/h + 3 mg/kg) drink. Movement characteristics, heart rate, ratings of perceived exertion (RPE), and countermovement jump (CMJ) height were measured during the protocol. CHO-C resulted in likely to very likely higher mean running speeds (effect size [ES] 0.43-0.75), distance in high-intensity running (ES 0.41-0.64), and mean sprint speeds (ES 0.39-1.04) compared with CHO. Heart rate was possibly to very likely higher (ES 0.32-0.74), and RPE was likely to very likely lower (ES -0.53 to 0.86) with CHO-C. There was a likely trivial to possibly higher CMJ in CHO-C compared with CHO (ES 0.07-0.25). The coingestion of carbohydrate with caffeine has an ergogenic effect to reduce the sense of effort and increase high-intensity running capability that might be used to enhance interchange running performance in elite rugby league players.